Effects of 11-Ketotestosterone on Development of the Previtellogenic Ovary in the Sterlet, Acipenser ruthenus - Wang, Wei; Zhu, Hua; Tian, ZhaoHui; Sun, Ai; Dong, Ying; Dong, Tian; Hu, HongXia (Frontiers in Endocrinology, 2020)
11-ketotestosterone (11-KT) is a non-aromatizable and the most potent androgen in a few teleost. It's been reported 11-KT in serum had a high concentration and increased sharply before the period of yolk deposition in females of few fishes. The aim of this study was to analyze the role of 11-KT both in vivo and in vitro on ovarian development, related gene expression levels, Vitellogenin (Vtg) synthesis and serum sex steroid concentrations in previtellogenic cultured sterlet (Acipenser ruthenus). Silastic strips embedded with 11-KT (5 or 25 mg/kg) were implanted in vivo for 30 days. Ovarian masculinization or sex reversal was not observed. Histological analysis showed that 11-KT promoted sterlet ovarian development in a dose-dependent manner. Vtg and testosterone (T) increased significantly, while 17β-estradiol (E2) decreased with no significant difference among groups. The expression of genes androgen receptor (ar), vtg and lipoprotein lipase (lpl) were significantly increased in liver. However, 11-KT had no effect on the expression of foxl2 and cyp19a1 in ovary. In vitro, after incubation with 11-KT (10 and 100 μM) for five days, both T and E2 concentrations increased in both hepatic explants and ovarian explants culture medium; the concentration of Vtg also increased in hepatic explants culture medium. The expression of ar, era, vtg and lpl increased significantly in hepatic explants. However, only the expression of era significantly increased in cultured ovarian explants. Altogether, these results suggest that 11-KT induced ovarian development, as well as Vtg and lipid synthesis, and could be an important factor facilitating the initiation of Vtg synthesis in the liver of the previtellogenic sterlet.